Manipulation and characterization of proopiomelanocortin (POMC) neurons in the hypothalamic regulation of energy balance - Dennison, Christina Suzanne, author; Hentges, Shane T., advisor; Partin, Kathy M., advisor; Pagliassotti, Michael J., committee member; Tamkun, Michael M., committee member; Vigh, Jozsef, committee member (Colorado State University. Libraries, 2015)
It is well documented that hypothalamic proopiomelanocortin (POMC) neurons are a critical component in the maintenance of energy balance. POMC neurons release peptide transmitters that modulate pathways involved in food intake, energy expenditure, and reward pathways. POMC peptide release can result in the inhibition of food intake and increased activation of these cells is thought to precipitate the development of anorexia in the activity-based anorexia (ABA) rodent model. Currently, the physiological underpinnings that drive the development of anorexia are not fully understood, but evidence suggests that POMC neurons are a likely contributor. The work presented in Chapter 2 of this dissertation provide further evidence that POMC neurons are activated during the early development of ABA and addresses whether this increase in POMC neuron activation is necessary for decreased food intake and body weight during ABA. POMC neurons were selectively inhibited during the onset of ABA. The results presented here indicate that POMC neuron activation facilitates suppression of food intake during the early stages of ABA. To determine if increased activation of POMC neurons is sufficient to induce lasting anorexia, in Chapter 3 POMC neurons were activated acutely and long-term to determine if activation of these cells alone is sufficient to initiate the development of anorexia. The data in Chapter 3 show that acute activation of POMC neurons decreases daily food intake. Prolonged activation of POMC neurons was able to give rise to long-term decreases in food intake under the proper conditions; but, the data from these experiments provide insight regarding methodological considerations that are important for long-term behavioral work in rodents. Activation or inhibition of POMC neurons through the approach used here could lead not only to altered release of peptides from these neurons, but also altered amino acid (AA) transmitter release. Unlike, the heavily studied peptides, there is little information regarding AA transmitters in POMC neurons and their effects on energy balance are not known. To begin to build a more comprehensive understanding of POMC neuron physiology, the work described in Chapter 4 characterized the AA transmitter phenotype of POMC neurons during postnatal development and investigated the role of glutamate release from POMC neurons. Data shown here indicate that the AA transmitter phenotype of POMC neurons remains plastic during early postnatal development. Given that young mice are more vulnerable to developing ABA relative to adult mice and that POMC neurons are involved in developmentally regulated events such as reproduction and maturation of feeding circuits the research described here could provide insight into sensitive periods that are more amenable to manipulating POMC neurons. The work in Chapter 4 also shows that glutamate release from POMC neurons is involved in regulating body weight in a sex- and diet-specific manner, which is the first documented example describing the function of AA transmitter release from POMC neurons. Taken together the research described here expand current understanding of how POMC neurons participate in the dysregulation of energy balance. This work also highlights the importance of AA transmitters in POMC neurons and provides insight for future work.
Keywords: energy balance; in situ hybridization; POMC; glutamate; designer receptors exclusively activated by designer drug; plasticity